A imagem feminina no ambiente doméstico em "O livro de possuídos" de Maria Lúcia Dal Farra - Santos, Edelaine Santana (2018)
This work is dedicated to the study of the book of poetry "Owned" by Maria Lúcia Dal Farra with the pretension of analyzing the female image in society linked to the home environment. Based on the gender studies, this work intends to evaluate the influence of the patriarchal power to maintain the image of the woman linked to domestic tasks, and the stereotypes that revolve around this gender, which leaves the woman in a submissive position to the man. Thus, the concepts of Roberto da Matta and Gaston Bachelard are applied to interpret the house space as a space of feminine protection and that has an intimate essence of the feminine, and Pierre Bourdieu that shows us the male domination over the feminine. In the first moment, the patriarchal conception and the feminine education are studied. In the second moment, we will work the domestic house environment as a private space for the feminine care, and in the third moment we will analyze the stereotypes that revolve around the feminine and the five poems of the book "Possuídos" of Maria Lúcia Dal Farra, being: "First Passos "," The nanny "," Cabbage "," Apple "and" Manga "emphasizing the discourse that denounce the existence of inferiority of the female gender to society and the opposition that the poems cause on these stereotypes, showing the woman with a freed being.